2021
DOI: 10.31235/osf.io/fbxwt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Network Approaches to Bullying and Victimization

Abstract: Social network research is the way to examine bullying as a group process. Cross-sectional network studies allow us to examine who bullies whom or who defends whom, as well as the agreement on these dyadic relationships. Longitudinal network studies allow us to particularly examine selection and influence processes. The longitudinal studies with the most power have shown that selection and influence processes play a role for bullies. For victims, selection and influence processes have been found in adolescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…These findings add to the growing body of research finding that peers, in particular friends, contribute to students' defending and bystanding behaviors. Whereas previous research showed that peers generally affect defending and bystanding behaviors, for example, due to perceived peer normative pressure (Pozzoli and Gini, 2010) or peer group norms , consistent with prior network research on defending behavior (Veenstra and Huitsing, 2021) the findings suggest that friends influence one another's defending. Finding an effect of friend influence on bystanding behavior is novel, however, but aligns with network research finding friends also influencing the other bullying roles (i.e., bullying behavior and peer victimization; see Veenstra and Huitsing, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These findings add to the growing body of research finding that peers, in particular friends, contribute to students' defending and bystanding behaviors. Whereas previous research showed that peers generally affect defending and bystanding behaviors, for example, due to perceived peer normative pressure (Pozzoli and Gini, 2010) or peer group norms , consistent with prior network research on defending behavior (Veenstra and Huitsing, 2021) the findings suggest that friends influence one another's defending. Finding an effect of friend influence on bystanding behavior is novel, however, but aligns with network research finding friends also influencing the other bullying roles (i.e., bullying behavior and peer victimization; see Veenstra and Huitsing, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…By acknowledging that bullying is a group phenomenon and occurs in the presence of peer witnesses, developmental and peer relationships research have put great effort into understanding the role of peers in the bullying process in recent years (Salmivalli, 2010). However, most work has examined defending and bystanding and its antecedents without consideration of peer-network influences, with very few exceptions (Veenstra and Huitsing, 2021). Thus, researchers still know very little about the interpersonal mechanisms and peer group dynamics through which peers shape defending and bystanding behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we lack information concerning why students engage in defending behavior. Information about the characteristics of the victims and defenders might provide additional information about why defending relationships between victims and defenders are formed (Veenstra & Huitsing, 2021). This investigation would benefit from taking a broader perspective, by not only asking the victim about their defenders but also asking bullies about their victims and asking defenders which victims they support.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…Although peernominated measures are highly appreciated and used in social behavior research (van den Berg et al, 2015), they have limitations as well (e.g., Olweus, 2013). Specifically, the peer nominations used in our study can be considered as measures of behavioral reputation rather than the relational network reality (Stassen Berger, 2007;Veenstra and Huitsing, 2021). Behavioral reputations are often quite stable and changing peers' opinions on a student's reputation takes time (Davis and Lease, 2007); hence, it might be more difficult for teachers to affect peer nominations of bullying.…”
Section: Discussionmentioning
confidence: 99%